Dinamika Peninjauan Kurikulum Madrasah Diniyah Tarbiyatul Athfal (MDTA) Gontor - Lutfi Najamul Fikri (IAIN Ponorogo, 2016)
Abstract: Curriculum as the educational design has a central position in a learning activity. The curriculum greatly influence the success of the process and learning outcomes. Therefore, the curriculum should be developed according to the students environment, the demands of work, the development of today's life and future. According to the importance of the curriculum, this research focuses on the dynamics of curriculum development in MDTA Gontor Mlarak Ponorogo. By using a qualitative approach, this study produced three findings: (1) A review of the curriculum in MDTA Gontor is a strategic implementation to achieve the vision, mission, and goals of the institution. (2) The dynamics of the curriculum since the founding of MDTA Gontor from year to year is evolutionary which takes place gradually. (3) A review of the curriculum in MDTA Gontor consists of three Phase. The first plan includes: the formulation of the vision, mission and objectives, curriculum material selection or determination of the structure of the curriculum. Second, implementation of the curriculum with emphasis on strengthening cognitive (mind) psychomotor (physical) and affective (spiritual) students. Thirdly, evaluation which includes four dimensions: the use of the curriculum by teachers, curriculum design, learning outcomes of students and the curriculum system.Abstrak: Kurikulum sebagai rancangan pendidikan memiliki kedudukan yang sangat sentral dalam sebuah kegiatan pembelajaran. Kurikulum sangat berpengaruh terhadap keberhasilan proses dan hasil belajar. Oleh karena itu, kurikulum hendaknya dikembangkan sesuai dengan lingkungan murid, tuntutan pekerjaan, perkembangan kehidupan masa kini dan masa yang akan datang. Mengingat pentingnya kurikulum tersebut, penelitian ini memfokuskan pada dinamika pengembangan kurikulum di MDTA Gontor Mlarak Ponorogo. Dengan menggunakan pendekatan kualitatif, penelitian ini menghasilkan temuan: (1) Peninjauan kurikulum di MDTA Gontor merupakan implementasi strategi pencapaian visi, misi, dan tujuan lembaga. (2) Dinamika kurikulum sejak tahun berdirinya MDTA Gontor dari tahun ke tahun bersifat evolusioner yang berlangsung secara secara bertahap. (3) Peninjauan kurikulum di MDTA Gontor terdiri dari tiga Tahap. Pertama perencanaan yang meliputi: perumusan visi, misi dan tujuan, pemilihan materi kurikulum atau penetapan struktur kurikulum. Kedua, Pelaksanaan kurikulum dengan menekankan penguatan aspek kognitif (akal) psikomotorik (jasmani) dan afektif (rohani) siswa. Ketiga, evaluasi yang meliputi empat dimensi: penggunaan kurikulum oleh guru, desain kurikulum, hasil belajar peserta didik dan sistem kurikulum.